Building capacity through school based engagement on dam safety program in Cameron Highlands - Sabri Muda, Rahsidi; Tukiman, Izawati; Mohd. Hussain, Mohd. Ramzi; Rabe, Noor Suzilawati (Springer, Singapore, 2020)
Melaka Declaration on Disaster Risk Reduction in Malaysia (2011) captured the future direction of the country on disaster risk reduction as well as its efforts towards implementing the priority areas for the Sendai Framework, 2015–2030 and together with SDG11 (Sustainable Goals 11: Sustainable Cities and Communities) and SDG13 (Sustainable Goals 13: Climate Change). Therefore, in supporting the government initiatives, Tenaga Nasional Berhad (TNB) as the owner of most of the largest dams in Malaysia, has put into action an initiative in community engagement program for disaster risk awareness campaign in the context to increase the community awareness and preparedness. This paper presents a school-based engagement as part of the community engagement program conducted for Pos Telanok community in Cameron Highlands. This was the pioneer program, which was conducted at SK Telanok involving 290 students and staffs. Programs was organised in a few phases starting from November 2018 including awareness campaign, Dam Safety Day, evacuation exercises and CSR. These activities are aimed to educate the school community in Pos Telanok who are vulnerable to flood risk in the event of dam failure, to be more prepared and resilient to face the disasters. The program provides exposure to schoolchildren and staffs on the right actions to be taken during emergencies. On the other hand, the program to strengthen the preparedness of dam owner, local authorities and emergency responders involved with local communities during emergencies.